2000
DOI: 10.2307/2656745
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of four abiotic factors on the germination of salt marsh annuals

Abstract: Interspecific differences in responsiveness to temperature, photoperiod, soil salinity, and soil moisture confirm the hypothesis that abiotic factors differentially affect the germination of salt marsh plants. In growth chamber experiments, four of eight annual species responded to small differences in temperature or photoperiod. Increasing soil salinity decreased the final proportion of seeds germinating and slowed germination for each of the seven species tested. Higher soil moisture increased the proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
66
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 30 publications
5
66
0
Order By: Relevance
“…Similar trends have been found in several species of Atriplex, in some annual halophytes (Noe et al 2000;Debez et al 2001) and in Nicotiana tabacum (Niknam et al 2004). We found twenty-six-days salt treatment inhibited germination without damaging the seeds when the seeds, which did not germinate, were dissected to identify the viable seeds.…”
Section: Discussionsupporting
confidence: 79%
“…Similar trends have been found in several species of Atriplex, in some annual halophytes (Noe et al 2000;Debez et al 2001) and in Nicotiana tabacum (Niknam et al 2004). We found twenty-six-days salt treatment inhibited germination without damaging the seeds when the seeds, which did not germinate, were dissected to identify the viable seeds.…”
Section: Discussionsupporting
confidence: 79%
“…In general, our results corroborate those of Noe and Zedler (2000), who were not able to explain the distribution of ten salt marsh species on the basis of differential germination requirements. Rather, the abundance pattern of the three fescue species in nature appears to be related to differential establishment of seedlings.…”
Section: Discussionsupporting
confidence: 82%
“…The finding confirms that of Debez et al (2004) for another Tunisian ecotype of the same species. Actually, several studies have shown that halophytes are salt-sensitive at the earliest establishment stage; however, they acquire halophytic features during autotrophic stage of development (Katembe et al 1998;Noe and Zedler 2000;Ungar 1996).…”
Section: Discussionmentioning
confidence: 99%